2014
DOI: 10.1186/1471-2180-14-52
|View full text |Cite
|
Sign up to set email alerts
|

Reliable differentiation of Meyerozyma guilliermondii from Meyerozyma caribbica by internal transcribed spacer restriction fingerprinting

Abstract: BackgroundMeyerozyma guilliermondii (anamorph Candida guilliermondii) and Meyerozyma caribbica (anamorph Candida fermentati) are closely related species of the genetically heterogenous M. guilliermondii complex. Conventional phenotypic methods frequently misidentify the species within this complex and also with other species of the Saccharomycotina CTG clade. Even the long-established sequencing of large subunit (LSU) rRNA gene remains ambiguous. We also faced similar problem during identification of yeast iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 56 publications
1
38
0
5
Order By: Relevance
“…Total yield of ethanol from M. guilliermondii and S. cerevisiae using molasses medium (initial reducing sugar concentration of 18.3 w/v%) revealed that M. guilliermondii produced higher volumes (10 ± 0.2 mg/ml) than that of S. cerevisiae (9 ± 0.2 mg/ml) at 96 hours (figure 7). The demand curve for assortment of low, medium to high alcohol content wines has informed the decision to study various tactics towards the production of low-medium [27]. Data from this study suggests that the non-Saccharomyces yeast; Meyerozyma guilliermondi, can be applied towards the production of various categories of wine.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Total yield of ethanol from M. guilliermondii and S. cerevisiae using molasses medium (initial reducing sugar concentration of 18.3 w/v%) revealed that M. guilliermondii produced higher volumes (10 ± 0.2 mg/ml) than that of S. cerevisiae (9 ± 0.2 mg/ml) at 96 hours (figure 7). The demand curve for assortment of low, medium to high alcohol content wines has informed the decision to study various tactics towards the production of low-medium [27]. Data from this study suggests that the non-Saccharomyces yeast; Meyerozyma guilliermondi, can be applied towards the production of various categories of wine.…”
Section: Discussionmentioning
confidence: 97%
“…Kluyveromyces marxianus [19], [20], Pichia kudriavzevii [21], [22], Dekkera bruxellensis [23], Zygosaccharomyces bailii [24]. Meyerozyma guilliermondii, a telemorph of Candida guilliermondii or wine yeast is one of such promising non Saccharomyces yeasts obtained from environmental samples with unique biotechnological applications and biological control potential [25], [26], [27], [28]. This yeast specie is known for its ease of consumption of xylose, naturally converting it to xylitol [29], [30].…”
Section: Introductionmentioning
confidence: 99%
“…Because these genetically related species are difficult to identify by conventional methods, molecular techniques are more suitable for their differentiation (24,30). ITS sequence analysis has been widely used as the gold standard for yeast species identification and for phylogenetic analysis (24,25,38).…”
Section: Discussionmentioning
confidence: 99%
“…Molecular methods such as PCR-restriction fragment length polymorphism (RFLP), real-time PCR, Luminex techniques, electrophoretic karyotyping, and PCR with type-specific primers have been developed to distinguish some of these species, but other species were not involved in those studies (30)(31)(32)(33). Matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) is a promising technique that works well to distinguish yeast species, although a few closely related species (such as C. fermentati) may still be misidentified (34)(35)(36).…”
mentioning
confidence: 99%
“…São positivas para os testes de urease e azul de diazônio B (Boekhout & Fell, 1998 Espécies do gênero Meyerozyma são geneticamente próximas formando um complexo de espécies, possuem importância médica, biotecnológica e potencial para uso em controle biológico. M. guilliermondi e M. caribbica são extremamente difíceis para diferenciar por métodos fenotípicos, e as sequências provenientes do domínio D1/D2 falha ao discriminar essas duas espécies, sendo necessário uma análise concatenada com a região ITS para separação das espécies (Romi et al, 2014), fato observado nos isolados identificados no clado Meyerozyma.…”
Section: Filo Basidiomycotaunclassified